Additional 1 MVA transformer for new turbo chiller at HGST plant, Biñan Laguna - Terrenal, Jayme B. (Professional Regulation Commission, 2015)
This Technical Report documents the project: Additional 1 MVA transformer for new turbo chiller at HGST plant, Biñan Laguna. The additional installations includes provisions of civil and electro-mechanical works necessary to address existing chilled water capacity problems to support HGA Mindanao Lines Primary Utility projects. Electrical works includes design, supply and installation of power supply for the additional turbo chiller unit and auxiliaries (Transformer, Switchgear, MCC panel and controls)